Answer:
The simplest form of (a + b - c )(a + b + c ) is a² + 2ab + b² - c²
Explanation:
* Lets revise how to multiply two brackets with three terms
∵ (a + b - c)(a + b + c)
- Multiply the first term of the first bracket by the three terms of the
second bracket
∵ a × a = a²
∵ a × b = ab
∵ a × c = ac
- Then multiply the second term in the first bracket by the three terms
of the second bracket
∵ b × a = ba
∵ b × b = b²
∴ b × c = bc
- Then multiply the third term term in the first bracket by the three terms
of the second bracket
∵ -c × a = -ca
∵ -c × b = -cb
∵ -c × c = -c²
- Now add all these terms together
∴ a² + ab + ac + ba + b² + bc + -ca + -cb + -c²
- We have like terms lets add them
∵ ab = ba , ac = ca , bc = cb
∴ a² + (ab + ba) + (ac + -ca) + (bc + -cb) + b² + -c²
∴ a² + 2ab + 0 + 0 + b² - c²
∴ a² + 2ab + b² - c²
∴ The simplest form of (a + b - c )(a + b + c ) is a² + 2ab + b² - c²